Daily fortified-synbiotic yogurt consumption facilitates appetite control in overweight and obese adults with metabolic syndrome during a weight-loss program: a 10-week randomized controlled trial - Mohammadi-Sartang, Mohsen; Mazloomi, Seyed Mohammad; Fararouie, Mohammad; Bedeltavana, Alireza; Famouri, Mandana; Mazloom, Zohreh (Progress in Nutrition, 2020)
Objective:Weight loss programm is known to increase the appetite and motivation to eat. The aim of the present study was to compare the effect of fortified-synbiotic yogurt (FSY) with calcium, whey protein and vitamin D with low-fat conventional yogurt (LFY) on appetite control in overweight/obese individuals during weight loss. Method and matrials: This was a randomized, double-blinded, parallel-arm, 10-week study. Participants were randomly allocated to two groups receiving either two servings (2×250 g)/day of a fortified synbiotic yogurt (FSY) with whey protein, calcium, and vitamin D (n=44) or a low-fat conventional yogurt (LFY) (n=43). All participants were put on a caloric-restricted diet throughout the 10-week study. Fasting Visual Analogue Scale (VAS) was used to measure subjective sensations of appetite in before commencing the study, at weeks 5 and 10 of the study. Fasting plasma concentrations of ghrelin were measured as well. Result: Both groups showed a significant (P